Tunda-Tunda Bamban Dalam Kebudayaan Masyarakat Melayu Tamiang di Aceh (Analisis Wacana Teks, Koteks, dan Konteks) - Abdul Gapur; Rivai Baiquni; Mhd. Pujiono (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2018)
This research discusses about kid’s playing song tunda-tunda bamban in Melayu Tamiang society. This research is kind of qualitative approach by using descriptive method. The data were taken from field research as the result of observation and directly interview toward informant of Melayu Tamiang society in Kampong Batu Aru, District Bandar Pusaka, Province Aceh. In analyzing function and meaning of the song, it is used theory of context and semiotics. Furthermore, the function of the song in society is analyzed by using Easman’s etnoscience theory. The result of research is found that kid’s playing song tunda-tunda bamban is the song for starting and during the game. The functions of song tunda-tunda bamban are such consolation, kid’s education media, application of societies’ norms, social control and strenghten the bounding of fraternity.